The efficiency cost of protective measures in climate policy - Christoph Böhringer; Xaquin Garcia-Muros; Ignacio Cazcarro; I\~naki Arto (University of Oldenburg, Department of Economics, 2016)
Despite recent achievements towards a global climate agreement, climate action to reduce greenhouse gas emissions remains quite heterogeneous across countries. Energy-intensive and trade-exposed (EITE) industries in industrialized countries are particularly concerned on stringent domestic emission pricing that may put them at a competitive disadvantage with respect to producers of similar goods in other countries without or only quite lenient emission regulation. This paper focuses on climate policy analysis for the United States of America (US) and compares the economic implications of four alternative protective measures for US EITE industries: (i) output-based rebates, (ii) exemptions from emission pricing, (iii) energy intensity standards, and (iv) carbon intensity standards. Based on simulations with a large-scale computable general equilibrium model for the global economy we quantify how these protective measures affect competitiveness of US EITE industries. We find that while protective measures can attenuate adverse competitiveness impacts measured in terms of common sector-specific competitiveness indicators, they run the risk of making US emission reduction much more costly than uniform emission pricing stand-alone. In fact, the cost increase is associated with negative income effects such that the gains of protective measures for EITE exports may be more than compensated through losses in domestic EITE demand.
Keywords: D21; H23; D58; 330; Unilateral climate policy; competitiveness; computable general equilibrium